2007
DOI: 10.1556/avet.55.2007.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tiletamine-zolazepam anaesthesia on plasma antioxidative status and some haematological parameters in sheep

Abstract: It is not clear whether the anaesthetic agents tiletamine and zolazepam have antioxidant or pro-oxidant effects. Therefore, this study was carried out to investigate the effects of tiletamine-zolazepam anaesthesia on oxidant/antioxidant status in blood plasma and on haematological parameters in 10 healthy Awassi ewes. The tiletamine-zolazepam combination was administrated in a dose of 7.5 mg/kg intramuscularly. The animals were spontaneously breathing air during the procedure. Blood samples were collected by j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…However, other studies examining the use of tiletamine-zolazepam (Ceylan et al 2007) or its combination with xylazine in sheep (Aydilek 2007) and gazelles (Yaralioglu-Gurgoze et al 2005) demonstrated an increase in MDA concentrations, similar to the results of our study. Based on the fact that MDA is one of the end products of lipid peroxidation, and is both an indicator and effector of oxidative stress (Sivaci et al 2006) our study may support the fact that oxygen free radicals are released upon administration of TZXT.…”
Section: Discussionsupporting
confidence: 91%
“…However, other studies examining the use of tiletamine-zolazepam (Ceylan et al 2007) or its combination with xylazine in sheep (Aydilek 2007) and gazelles (Yaralioglu-Gurgoze et al 2005) demonstrated an increase in MDA concentrations, similar to the results of our study. Based on the fact that MDA is one of the end products of lipid peroxidation, and is both an indicator and effector of oxidative stress (Sivaci et al 2006) our study may support the fact that oxygen free radicals are released upon administration of TZXT.…”
Section: Discussionsupporting
confidence: 91%
“…Ceylan et al [7] found a decrease in hemoglobin 30 min after intramuscular injection of tiletamin and zolazepam to sheep, but the level was normalized after 60 min. In the time-course study, the hemoglobin did not return to baseline within the 105 min the study lasted; on the contrary, the hemoglobin continued to decrease, and after 30 min, a decrease was also observed in the non-anesthetized group.…”
Section: Discussionmentioning
confidence: 99%
“…Ceylan et al (2007b) reported that tiletamine-zolozepam anaesthesia alone induced lipid peroxidation in plasma of sheep. Similarly, a significant elevation in the MDA levels, index of lipid peroxidation in response to both anaesthetic administrations was noticed in the current study (Table 1).…”
Section: Discussionmentioning
confidence: 99%